Judaica reference sources : a selective, annotated bibliographic guide - Cutter, Charles (Denali Press, 1993)
This reference provides an outstanding resource for Holocaust materials in print, as presented in Chapter 18. Included are annotated listings of archival resources, atlases and gazetteers, bibliography, directories, encyclopedias and filmography.